A new ergosterol analog, a new bis-anthraquinone and anti-obesity activity of anthraquinones from the marine sponge-associated fungus Talaromyces stipitatus KUFA 0207 - Noinart J. (2017)
A new ergosterol analog, talarosterone (1) and a new bis-anthraquinone derivative (3) were isolated, together with ten known compounds including palmitic acid, ergosta-4,6,8(14),22- tetraen-3-one, ergosterol-5,8-endoperoxide, cyathisterone (2), emodin (4a), questinol (4b), citreorosein (4c), fallacinol (4d), rheoemodin (4e) and secalonic acid A (5), from the ethyl acetate extract of the culture of the marine sponge-associated fungus Talaromyces stipitatus KUFA 0207. The structures of the new compounds were established based on extensive 1D and 2D spectral analysis, and in the case of talarosterone (1), the absolute configurations of its stereogenic carbons were determined by X-ray crystallographic analysis. The structure and stereochemistry of cyathisterone (2) was also confirmed by X-ray analysis. The anthraquinones 4a-e and secalonic acid A (5) were tested for their anti-obesity activity using the zebrafish Nile red assay. Only citreorosein (4c) and questinol (4b) exhibited significant anti-obesity activity, while emodin (4a) and secalonic acid A (5) caused toxicity (death) for all exposed zebrafish larvae after 24 h. © 2017 by the authors. Licensee MDPI.